Modelling Bottleneck Factors In A Production Line Using Hybrid Approach - Desa, Wan Laailatul Hanim Mat (2016)
A bottleneck can occur in almost all business organizations, either services or manufacturing operations. In manufacturing sector, bottleneck normally occurs due to repetitive failures in the flow of production system. Besides that, there are several factors that can cause bottleneck events in the production line, such as long waiting time, huge backlog and high stress level. These bottleneck factors can reduce the throughput rate in the production line and negatively affect the production costs. Therefore, it should be tackled for a high production system performance and a smooth flow of products. Because of that, there is a need for the manufacturers to find ways in managing the bottleneck factors. In general, bottlenecks can be caused by tangible and intangible factors. However, the intangible factors have received less attention by the previous researchers. Most previous works had focused on tangible factor such as number of throughput but lack in intangible such as on workers stress level. Thus, this research investigates the intangible factors which emphasizes on human factor particularly in understanding the effect of absenteeism in the production line. In addition, this study also identifies causes of bottleneck in illustrating the relationship between human factors and production line. Absenteeism refers to a situation when the available manpower is less than the number of manpower needed on the production line. This human factor plays an important role in determining the production rate. In this thesis, a hybrid simulation model is used to analyse the absenteeism problem in an aircraft composite manufacturing by integrating a Discrete Event Simulation (DES) and a System Dynamics (SD) models which namely as Hybrid Simulation Based Bottleneck Management (HSBBM). To analyse the effect of absenteeism, the amount of throughput, waiting time, work in process (WIP) and cycle time are analysed in various scenarios of production planning. The result shows the number of absentees at production line increase the workload to the available worker and gives effect to the production rate. By considering the absenteeism, the number of throughput decrease 12.67% compared to the production plan indicating that the hybrid model is able to represent more realistic situation when involving human factor. In conclusion, the developed hybrid model can be used to visualise and quantify the impacts of human behaviour that lead to bottlenecks and able to assist the management to generate more relevant production plan.